FPGA based embedded system developer's guide - Raj, A. Arockia Bazil (CRC Press, Taylor & Francis, 2018)
The book covers various aspects of VHDL programming and FPGA interfacing with examples and sample codes giving an overview of VLSI technology, digital circuits design with VHDL, programming, components, functions and procedures, and arithmetic designs followed by coverage of the core of external I/O programming, algorithmic state machine based system design, and real-world interfacing examples. Aims to be a quick reference guide to design digital architecture in the FPGA and develop system with RTC, data transmission protocols.